The interplay among familial risk, narrative coherence, and emotional problems from early to middle childhood - Sticca, Fabio; Gasser-Haas, Olivia; Wustmann Seiler, Corina (Frontiers in Psychology, 2023)
The present study is a longitudinal extension (long-term follow-up) of a previous study examining the promotive and protective role of children’s narrative coherence in the association between early familial risk factors and children’s emotional problems from early to middle childhood. A total of 293 (T1; Mage = 2.81), 239 (T2; Mage = 3.76), and 189 (long-term follow-up T3; Mage = 9.69) children from 25 childcare centers participated in this study. Familial risk factors were assessed at T1 using a caregiver interview and questionnaire. Narrative coherence was assessed using the McArthur Story Stem Battery that was administered to the children at T2. Children’s emotional problems were rated by the caregivers and by their teachers at T2 and T3. Results suggest that familial risk factors are linked to more emotional problems both in the short-term (T2) and the long-term (T3). Further, although some of the effects of relevant magnitude did not reach statistical significance, results pertaining to the role of narrative coherence indicate that it might have a promotive and protective effect in the short term as well as a promotive effect in the long term. These findings point to the relevance of children’s narrative coherence as a cognitive ability and personality factor that contributes to more positive development and to better coping with adverse familial experiences.